Nursing leadership and management for patient safety and quality care - Murray, Elizabeth J. (Philadelphia, PA : F.A. Davis Company, 2022)
'The underpinnings of this book are evidence-based practice, safety, quality, and effective nursing care. The book will assist students to understand a current perspective of nursing leadership and management theories, concepts, and principles. Evidence-based content is presented on topics relevant in today's ever-changing health-care environment, such as contemporary leadership and management theories, managing ethical and legal issues, leading and managing effectively in a culture of safety, improving and managing quality care, building and managing a sustainable workforce, leading change and managing conflict, creating and sustaining a healthy work environment, and managing resources'--
Core competencies for safe and quality nursing care -- Health-care environment and health policy -- Theories and principles of nursing leadership and management -- Ethical aspects of nursing practice -- Legal aspects of nursing practice -- Critical thinking, decision making, and clinical reasoning -- High-reliability health-care organizations -- Effective communication -- Improving and managing safe and quality care -- Information technology for safe and quality patient care -- Creating and managing a sustainable workforce -- Creating and sustaining a healthy work environment -- Organizing patient care and staffing for patient safety -- Delegating effectively -- Leading change and managing conflict -- Managing finances -- Transitioning from student to professional nurse and beyond.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
OCLC control number change
Keywords: Nursing services -- Administration; Nurse administrators; Leadership; Nursing Care -- standards; Nursing Care -- organization & administration; Patient Safety -- standards; Quality Assurance, Health Care -- methods; Leadership; Nurse's Role; Leadership; Leadership; Electronic books